Typification and threat assessment of Jasminum parkeri (Oleaceae), a point endemic and critically endangered species of Indian Western Himalaya - Srivastava, Amber; Wagh, Vijay V.; Srivastava, S. K. (Phytotaxa, 2023)
While assessing the threat status and conservational approach of Jasminum parkeri Dunn, an endemic and threatened taxon in Indian Western Himalaya, it has been noticed that the name of this species has not been typified so far. This article deals with the lectotypification of Jasminum parkeri and conservation efforts of this highly habitat specific species.